In vivo indexes of platelet and vascular function during fish-oil administration in patients with atherosclerosis - Knapp, H.R; Reilly, I.A.G; Alessandrini, P; FitzGerald, G.A (The New England journal of medicine, 1986)
A 1-month study employing a simulated Eskimo diet of fish oil containing the N-3 polyunsaturated fatty acid, eicosapentaenoate (EP), assessed its beneficial effects in 6 peripheral vascular disease patients vs. 7 normal control subjects. Fish oil supplementation using a dose that simulates an Eskimo diet lowered the elevated excretion of 2,3-dinor-thromboxane B2 in patients with severe atherosclerosis (AS). The results provide evidence that biologically inert thromboxane A3 is formed from EP in vivo. Despite a 1-month high fish oil supplementation, however, the formation of the potent vasoconstrictor and platelet agonist, thromboxane A2, was not completely inhibited. The possible implications of these results for treating AS patients are discussed.(wz)